2017
DOI: 10.17503/agrivita.v39i2.694
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Indonesian Physic Nut (J. curcas) Based on Molecular Marker

Abstract: Various reports of molecular genetic diversity evaluation of physic nut (J. curcas) have given inconsistent results. Part of the reasons were because of the used of unrealiable markers. This study was conducted to evaluate genetic diversity of Indonesian physic nut germplasm using four types of molecular markers (RAPD, ISSR, SSR and SCAR markers). Twenty four J. curcas accessions planted in Pakuwon, Sukabumi, with various phenotypes were evaluated. Twenty eight SSR marker loci yielded monomorphic allele patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Polymorphism and genetic information provided by ISSR technique can be complemented with information from phenotypic and biochemical characterization, and thus be able to elucidate in a clearer way the intricate relationships and interactions that occur in most materials to assess their intraspecific diversity on a much finer scale [39]. In plants of J. curcas, the genetic diversity of accessions has been evaluated in populations of India and Brazil [9] [10] [40], Taiwan [11], South America (Costa Rica) [41], Africa and Asia [42], Indonesia [43]. These studies have revealed a low diversity attributed to the origin of plant material via vegetative propagation, which increases the possibility that germplasm banks store plants of identical provenance [40].…”
Section: Issr Molecular Marker Diversitymentioning
confidence: 99%
“…Polymorphism and genetic information provided by ISSR technique can be complemented with information from phenotypic and biochemical characterization, and thus be able to elucidate in a clearer way the intricate relationships and interactions that occur in most materials to assess their intraspecific diversity on a much finer scale [39]. In plants of J. curcas, the genetic diversity of accessions has been evaluated in populations of India and Brazil [9] [10] [40], Taiwan [11], South America (Costa Rica) [41], Africa and Asia [42], Indonesia [43]. These studies have revealed a low diversity attributed to the origin of plant material via vegetative propagation, which increases the possibility that germplasm banks store plants of identical provenance [40].…”
Section: Issr Molecular Marker Diversitymentioning
confidence: 99%
“…Unfortunately, a report has also indicated that Indonesian J. curcas genetic diversity was low (Saptadi et al 2017). Moreover, J. curcas breeding activities using such a narrow genetic base will not be efficient since the genetic gain for each breeding cycle will be low (Acquaah 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, numerous studies have shown low-level genetic diversity among the J. curcas accessions (Saptadi et al 2011;Saptadi et al 2017). Breeding for improved J. curcas varieties requires the availability of more diverse genetic materials than those available in the germplasm collection; thus, increasing the genetic diversity of J. curcas is a priority.…”
Section: Introductionmentioning
confidence: 99%
“…SSR markers have been widely used for evaluation of the Jatropha spp. germplasm genetic diversity (Mastan et al 2012;Maurya et al 2013;Montes et al 2014;Sanou et al 2015;Saptadi et al 2017). Even though these SSR markers were developed based on the J. curcas genome, they may also be useful for other Jatropha species (Sudheer et al 2011;Kumar Yadav et al 2011).…”
Section: Introductionmentioning
confidence: 99%